Efektivitas Protokol Kyoto Dalam Mereduksi Emisi Gas Rumah Kaca Di Indonesia - Ida Susilowati; S.Thoriq Musthofa Ahmad; Thoriq Faturrahman; Regga Fajar Hidayat (JOURNAL of LEGAL RESEARCH, 2022)
Global warming has become a global issue related to the environment, because of its impact on all countries today. The Kyoto Protocol is an international agreement that focuses on the environment, as an effort to reduce greenhouse gas emissions that have an impact on global warming. This study aims to analyze the effectiveness of the Kyoto Protocol as an effort to reduce greenhouse gas emissions in Indonesia. This research is a type of qualitative research with a case study method about the efforts to reduce greenhouse gas emissions in Indonesia through the Kyoto Protocol. The results of this study indicate that the Kyoto Protocol is considered ineffective in reducing greenhouse gas emissions in Indonesia, even though Indonesia has implemented it through technology transfer and coordination in the application of biofuels to reduce carbon emissions. This is indicated by the level of damage or loss of Indonesia’s forests to 2.8 million ha/year after the implementation of the Kyoto Protocol in 2006-2007. As an international treaty, the Kyoto Protocol does not have a compulsive enforcement mechanism. So that the implementation of the Kyoto Protocol as an international agreement will not be effective, f it is not accompanied by consistency and consequences for all member countries in its implementation.